The language of prophetic eschatology in the Old Testament - Wren, B (1968)
﻿ The INTRODUCTION sets out the two major aims of the thesis. The first is to evolve a precise and economical terminology for describing the language of prophetic eschatology and to find objective criteria for description, the problem being how to decide whether such language is intended literally or otherwise. The second aim is to show that and how the prophets use nonliteral poetic imagery, not for comment or decoration, but in attempts to sway their audience, present condensed argument or assertion, and show contemporary situations in a new light. The main lines of approach in subsequent chapters are then sketched out. [Continued in text ...]